Corporate social responsibility employment narratives: a linguistic analysis. Issue 6 (23rd July 2019) - Li, Zhongtian; Haque, Shamima
Abstract : Purpose: The purpose of this paper is twofold: first, it investigates whether and to what extent "linguistic hedging", an impression management form of linguistic expression that conveys an ambiguous level of commitment, is used in corporate social responsibility (CSR) employment narratives; and second, it explores whether there is any difference in the use of linguistic hedging between written and spoken corporate forms of language. It mobilises these objectives by examining employee-related narratives made by electronic manufacturing services (EMS) providers domiciled in Taiwan, in the context of labour malpractice incidents. Design/methodology/approach: Two groups of data are examined: corporate responsibility reports (written language) and interviews and speeches of corporate founders and senior executives (spoken language). The research sample is ten Taiwanese EMS firms, all of which attracted public criticism and scrutiny due to a series of employee-related incidents. The sample period is between 2009 and 2013. Linguistic hedging is measured quantitatively by the relative word frequency of hedges, using the concordance software ANTCONC, with findings interpreted through the lens of legitimacy theory and impression management. Findings: The study found that hedging was evident in CSR narratives. The EMS providers in Taiwan appeared to use hedging in employee-related disclosures to manage legitimacy challenges due to employee-related incidents that had happened in their assembly plants. The adjustments in employee-related disclosures made by the EMS firms as a legitimation strategy can be seen as a rhetoric device of impression management or a form of symbolic legitimation to persuade society to restore their legitimacy status. Further, overall hedging was more frequently used in spoken than written language, which suggests that rhetorical hedging in written narratives is more likely to be a deliberate choice of tactics to influence stakeholder perceptions and thereby manage corporate legitimacy. Originality/value: The study introduces a new analytical technique, linguistic hedging, into the CSR literature. This enriches research methods used in this field, providing more compelling insights into the relationship between the use of language and CSR narratives in the process of corporate legitimation of employee-related practices. This study thus provides a platform for future computational-linguistics studies in the field of CSR.